Legal Protection and Law Assistance to Notaries as a Public Official in Indonesia - Zaki, Muhammad; Saidin, Saidin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The value of the rule of law is a source of moral norms in the Indonesian legal system. According to Number 2 of 2014, the position of a notary has not accommodated legal protection and law assistance for a notary as a public official. The Notary Honorary Council's approval is the only limit for the judicial process, investigators, public prosecutors, or judges. Article 66, paragraph 1, states that in the judicial process, investigators, public prosecutors, or judges with the approval of the Notary Honorary Council are authorized to take copies of the minutes of the deed and/or letters attached to the minutes or the notary protocol in the notary's depository. The council also has the authority to summon the notary to participate in the examination of the notary deed or protocol under their custody. It is necessary to investigate further legal protection and efforts to provide legal assistance to notaries as public officials. This research employs normative legal methods and a statutory approach. Laws and legal regulations regarding the legal protection of notaries are the data analyzed in the article. The results of this study indicate that, as public officials, notaries have legal protection and legal assistance from the profession. The protection obtained includes nondisclosure rights and obligations. Notaries also receive protection from the Notary Honorary Council. Suppose any law enforcement officer wants to confiscate a copy of the minutes of the deed and/or the letters attached to the minutes of the deed or the notary's protocol in the notary's depository. The Notary Honorary Council must approve it. If law enforcement officers want to call a notary for a review of a notary deed or protocol in the notary's custody, the council must also approve this request. The provision of legal assistance to notaries in dealing with legal processes is given through the expansion of the authority of the Notary Honorary Council in Article 66, paragraph 2, of Law Number 2 of 2014 concerning Notary Positions.